Evaluation of University’s Place in the Adult Education Ecosystem - G. Z. Efimova; M. Yu. Semenov (Высшее образование в России)
The authors of the present paper conducted a comprehensive analysis of university place in the ecosystem of adult education, based on its characteristic functions, priorities of activity and emerging tensions. The participation of universities in the professional training of adults is analyzed. The research focus is projected on the assessment of the situation at the institutional (a university as a social institution) and organizational level (a university as a specific institution of higher education). A discussion of the prospects for transforming the place of higher institution in the ecosystem of adult education is presented. The study was conducted using a semiformalized interview method (n=36) with representatives of the commercial and public sector occupying key positions (heads and top management of universities, corporate universities, educational consulting organizations, providers of non-formal education services, etc.).   Main results. Several points of university positioning in the structure of adult education ecosystem are identified: 1) the university is the core of the educational ecosystem and holds this status; 2) the university occupies the central place of the educational ecosystem, but can lose this status by certain actions or inaction; 3) the university is not the core of the educational ecosystem and should not be; 4) the university is not the core of the educational ecosystem, but could become it. According to most experts, universities occupy a central place in the ecosystem of adult education and have a high potential to retain leadership positions, provided that the educational material is relevant and meets the demands of the labor market. At the same time, it is important to consider that some participants of the educational ecosystem (online platforms, corporate universities and others) are rapidly increasing their influence and implementing large-scale educational programs for the population. Universities, having a high level of public trust and being mainly responsible for fundamental professional education, are interested in accumulating the advantages of other participants of the educational ecosystem. It is optimal to present the university as a central hub of educational practices for the population, accumulating the advantages of other actors of the adult education ecosystem. The article is addressed to administrative and managerial staff of universities, representatives of executive authorities and the real sector of the economy, scientific and pedagogical staff and graduate students seeking to study lifelong learning of adults.